Database performance tuning handbook - Dunham, Jeff. (New York : McGraw-Hill, 1998)
Geared to database professionals who are responsible for optimizing database performance, Jeffrey Allan DunhamÕs Database Performance Tuning Handbook is a one-stop reference for tuning and tweaking the latest releases of all popular database management systems. Drawing on over 25 years experience in database tuning and performance, Dunham relates essential tips for optimizing Oracle 7.3, Sybase 11, Microsoft SQL Server 6.5, DB2 4.X, CA-IDMS release 14, and other popular database products. Other sections cover client/server systems, database planning, design and networking, mainframe blocking, buffering, coding and caching, PC files and buffers, advanced data management techniques, and more.
Ch. 1. Statistics Collection -- Ch. 2. Mainframe Blocking and Buffering -- Ch. 3. PC Files and Buffers -- Ch. 4. DB2 System Tuning -- Ch. 5. Logical Database Design -- Ch. 6. Microsoft SQL Server 6.5 Tuning -- Ch. 7. Oracle 7.3 Tuning -- Ch. 8. Microsoft Windows NT 4.0 Tuning -- Ch. 9. Microsoft Windows 95 Tuning -- Ch. 10. PC and Client/Server Program Coding -- Ch. 11. Sybase 11 Tuning -- Ch. 12. Mainframe Coding -- Ch. 13. Mainframe Sorts -- Ch. 14. CA-IDMS 12.x and 14.0 System Tuning -- Ch. 15. Mainframe Multilevel Caching -- Ch. 16. PC and Client/Server Caching -- Ch. 17. Communications and Networking -- Ch. 18. Advanced Techniques -- App. A. Cobol Coding Considerations -- App. B. RAD (Rapid Application Development) -- App. C. SAR and PSC Command Syntax on SYSTEM 5 and UNIX Systems -- App. D. Vendors and Products (in alphabetical order by vendor) -- App. E. CA-IDMS DML Command CPU Benchmark Program -- App. F. 12 Rules of Relational Database (a simplified version) -- App. G. Object Technology -- App. H. Capturing Statistics for SR8 Integrated Indexes Within Your Program -- App. I. Hiperspace and Dataspace Reference Materials -- App. J. CA-Clipper Command Benchmark Comparison -- App. K. Computational Test Programs (Mainframe and PC) -- App. L. Cobol Soundex Program -- App. M. Total Quality Management Terms -- App. N. Best Database Software Sites in the World -- App. O. CALCSPAC.SQL Procedure for Oracle Table Extents -- App. P. CA-IDMS SQL System -- App. Q. IDMSBCF Space -- App. R. SCO Unix Tuning.
Includes index.
Keywords: DATABASE MANAGEMENT -- HANDBOOKS, MANUALS, ETC